THE GOVERNMENT'S STRATEGIES FOR PROMOTING RELIGIOUS TOLERANCE IN A MULTICULTURAL SOCIETY - Karimullah, Suud Sarim; Arif Sugitanata (The Ministry of Religious Affairs, The Republic of Indonesia, 2023)
This study aims to analyze the innovative strategies implemented by the government to strengthen religious tolerance in a multicultural society. Facing the challenges of harmony and understanding between religions, the government's role in promoting religious tolerance is becoming increasingly important. This study uses library research methods and qualitative approaches with content analysis techniques to produce a comprehensive data analysis by the principles of qualitative research. The study results show that the government's effective strategy in promoting religious tolerance in multicultural societies includes inclusive policies, multicultural education, interfaith dialogue, law enforcement, and inter-agency cooperation. By implementing these strategies, multicultural societies can live harmoniously, respect each other, and build a peaceful religious life. To achieve peaceful religious life in a multicultural society, individuals, religious groups, governments, and social institutions must respect diversity and jointly promote harmony between religions. This collaboration will be key to realizing a peaceful and harmonious religious life.